STRUCTURE OF OUTCOMES AND FINISHING ATTACKS ON EUROPEAN WOMEN'S HANDBALL CHAMPIONSHIPS 2010 - Katarina Ohnjec (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The main goal of the study is to determine the structure of finalization in attack on team handball matches based on their outcome, and the type of ending that her players performed. The sample of entities in the present study is registered in the 2710 attack of 20 matches of European Women's Handball Championships 2010. in Denmark and Norway. The sample of variables are positive (goal is scored), negative (no goal and lost possession of the ball) and neutral (no goal, but the ball remains in the possession of the team) outcomes of attacks. Based on the registered frequency the total representation of the outcomes and finishing in the overall structure of the finalization of the attack is determined. These indicators suggest the overall Championship in realization average efficiency of 35% positive outcomes, 55% negative and 10% positive outcome. In implementing the finalization of attack mostly participate back court players, mainly left (LV-24%), then right (21%) and centre (20%) back court players. Line players have participated in the execution of ending the attack as follows: players on the right wing ended with a total of 13% of attacks, and only one percent less, or 12% of players on the left wing, while the pivot players ended in a total of 10% of attacks.